Nucleotide receptor P2RY4 is required for head formation via induction and maintenance of head organizer in Xenopus laevis. (1st August 2018) - Harata, Ayano; Hirakawa, Mika; Sakuma, Tetsushi; Yamamoto, Takashi; Hashimoto, Chikara
Abstract : Vertebrates have unique head structures that are mainly composed of the central nervous system, the neural crest, and placode cells. These head structures are brought about initially by the neural induction between the organizer and the prospective neuroectoderm at early gastrula stage. Purinergic receptors are activated by nucleotides released from cells and influence intracellular signaling pathways, such as phospholipase C and adenylate cyclase signaling pathways. As P2Y receptor is vertebrate‐specific and involved in head formation, we expect that its emergence may be related to the acquisition of vertebrate head during evolution. Here, we focused on the role of p2ry4 in early development in Xenopus laevis and found that p2ry4 was required for the establishment of the head organizer during neural induction and contributed to head formation. We showed that p2ry4 was expressed in the head organizer region and the prospective neuroectoderm at early gastrula stage, and was enriched in the head components. Disruption of p2ry4 function resulted in the small head phenotype and the reduced expression of marker genes specific for neuroectoderm and neural border at an early neurula stage. Furthermore, we examined the effect of p2ry4 disruption on the establishment of the head organizer and found that a reduction in the expression of head organizer genes, such as dkk1 and cerberus, and p2ry4 could also induce the ectopic expression of these marker genes. These results suggested that p2ry4 plays a key role in head organizer formation. Our study demonstrated a novel role of p2ry4 in early head development. Abstract : P2Y4 receptor is required for the formation of head organizer and function in the following induction process of neural and neural crest. We demonstrated a novel role of p2ry4 in early head development.